Formation of Au Nanoparticles in Liquid Cell Transmission Electron Microscopy: From a Systematic Study to Engineered Nanostructures - Zhang, Yucheng (Chem Mater, 2017)
[Image: see text] In this work, a systematic study of the effect of electron dose rate, solute concentration, imaging mode (broad beam vs scanning probe mode), and liquid cell setup (static vs flow mode) on the growth mechanism and the ultimate morphology of Au nanoparticles (NPs) was performed in chloroauric acid (HAuCl(4)) aqueous solutions using in situ liquid-cell TEM (LC-TEM). It was found that a diffusion limited growth dominates at high dose rates, especially for the solution with the lowest concentration (1 mM), resulting in formation of dendritic NPs. Growth of 2D Au plates driven by a reaction limited mechanism was only observed at low dose rates for the 1 mM solution. For the 5 mM and 20 mM solutions, reaction limited growth can still be induced at higher dose rates, due to abundance of the precursor available in the solutions, leading to formation of 2D plates or 3D faceted NPs. As a proof-of-concept, an Au nanostructure with a 3D faceted particle core and a dendritic shell can be in situ produced by simply tuning the electron dose in the 1 mM solution irradiated in a flow cell setup in the STEM mode. This work paves the way to study the growth of complex heteronanostructures composed of multiple elements in LC-TEM.